Pengaruh Media Visual Berbantuan Canva dan Assemblr Edu terhadap Hasil Belajar Ilmu Pengetahuan Alam pada Siswa Kelas III Sekolah Dasar Negeri 106156 Klumpang Kebun - Yulia Yulia; Layil Safitri; Emy Hariati (Medan Resource Center, 2026)
This study examined the effect of Canva and Assemblr Edu-assisted visual media on the Science learning outcomes of third-grade students at Public Elementary School 106156 Klumpang Kebun, Indonesia. The research was conducted in response to students' low Science achievement, which was associated with the limited use of innovative instructional media, resulting in difficulties in understanding abstract scientific concepts. A quantitative approach employing a quasi-experimental method with a Nonequivalent Control Group Design was adopted. The study involved 40 students divided into an experimental group and a control group selected through purposive sampling. Data were collected using pretests and posttests and analyzed through tests of normality, homogeneity, and the Independent Samples t-test. The findings revealed that the experimental group achieved a substantial improvement in learning outcomes, with the mean score increasing from 66.00 on the pretest to 77.00 on the posttest, outperforming the control group that received conventional instruction. Furthermore, hypothesis testing produced a significance value (Sig. 2-tailed) of 0.002, which was lower than the 0.05 significance level, indicating a statistically significant difference between the two groups. These findings demonstrate that integrating Canva and Assemblr Edu-assisted visual media into Science instruction significantly enhances students' learning outcomes and offers an effective approach for facilitating conceptual understanding at the elementary school level.